2012
DOI: 10.1158/0008-5472.can-11-3061
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Derived IGF Mediates Crosstalk between Bone and Breast Cancer Cells in Bony Metastases

Abstract: The continuous release of bone-stored growth factors following bone resorption promotes the colonization of circulating cancer cells. However, the precise role of each of the various growth factors remains unclear. In this study, we investigated the role of bone-derived insulin-like growth factor (IGF) in the development of bone metastases in an animal model of breast cancer. We found that local stimulation of calvarial bone resorption prior to cell inoculation stimulated subsequent bone metastases to that sit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 38 publications
6
72
0
Order By: Relevance
“…As for bone metastases, neutralizing antibody against IGF type I receptor (IGF-IR), but not other bone-secreted factors such as TGF-β, fibroblast growth factors (FGFs), and platelet-derived growth factors (PDGFs), blocks breast cancer bone anchorage. This supports a unique and important role of bone-derived IGF-I in the crosstalk between the bone microenvironment and the cancer cells [95]. …”
Section: Homing To the Bonesupporting
confidence: 69%
“…As for bone metastases, neutralizing antibody against IGF type I receptor (IGF-IR), but not other bone-secreted factors such as TGF-β, fibroblast growth factors (FGFs), and platelet-derived growth factors (PDGFs), blocks breast cancer bone anchorage. This supports a unique and important role of bone-derived IGF-I in the crosstalk between the bone microenvironment and the cancer cells [95]. …”
Section: Homing To the Bonesupporting
confidence: 69%
“…Li et al further showed that androgen-deprivation can upregulate VEGF-C expression through down-regulation of the IGF-IR pathway and activate the forkhead transcriptional factor FOXO-1 (74). In bone metastasis, bone-derived IGF-I can bridge the crosstalk between bone and metastasized cancer cells via activation of the IGF-IR/Akt/NF-κB pathway (78). Therefore, disruption of IGF-IR and NK-kB pathways may represent a promising therapeutic intervention for bone metastasis, whereas co-targeting IGF-IR and VEGF may be more effective to treat lymphatic metastasis.…”
Section: Igf-ir Signaling In Prostate Cancer Metastasismentioning
confidence: 99%
“…Approximately 80% of patients with disseminated metastatic breast cancer develop skeletal metastases [2, 3], emphasizing that breast cancer has a propensity to metastasize to bone. Bone metastases from breast cancer are typically osteolytic and feature bone resorption [48]. In the bone microenvironment, breast cancer cells produce osteoclast (OC)-activating cytokines, including parathyroid hormone-related protein (PTH-rP), prostaglandin E 2 (PEG 2 ), and interleukin-11 (IL–11) [5], which can increase expression of receptor activator of nuclear factor-κB ligand (RANKL) by osteoblasts (OBs).…”
Section: Introductionmentioning
confidence: 99%